Kesalahan Interlingual Dalam Bahasa Inggris Oleh Siswa Kelas Tujuh Smp Jembatan Budaya - Wedananta, Kadek Adyatna (Jurnal Ilmiah Manajemen & Bisnis, 2017)
This study analyzes some Interlingual errors that occurred to seventh-grade students of SMP Jembatan Budaya who have low scores on each exam. That is why it is easy to find some of the Interlingual errors of these seventh-grade students. In addition, the use of second language acquisition or the use of L2 often occurs in the classroom as they learn L2 especially English. This can happen from teacher to student or student to teacher or can see when students make some written tasks. This study found evidence that English (L2) used still at the Interlanguage level (IL) because some students still had Interlingual errors when they used English (L2) such as the use of To Be, prepositions and adjectives/nouns. Therefore, the researchers found the strategy of school teachers to solve the problem of Interlingual errors by using Drill method that makes them do the repetition about the use of To Be, adjectives/nouns, etc. And the latter was a perspective on the relationship between Interlingual Errors with the businessman in the Global Era which was said to be closely related to the interest of foreign business clients when interacting with the business, if the businessman is speaking with good grammar and correctness then the business client of the foreign country will give plus points and assess the businessman as a smart and intelligent partner.Keywords: Second Language Acquisition, Interlingual Errors, Businessman in Era Global